Balance disorders: a review of patients at a specialized vestibular clinic - Wong, Kim Yew Richard; Zainal Abidin, Muhammad Hosni; Jamaluddin, Saiful Adli; S.M.A Abdul Rasheed, Shamim Rahman; Al- Hadeethi, Yahia F. Hussein (Kulliyyah of Medicine, International Islamic University Malaysia, 2022)
INTRODUCTION: With recent advancements in vestibular assessments, new ancillary tests can assist clinicians to better understand underlying cause of a balance problem. The recently established specialized vestibular clinic in Sultan Ahmad Shah Medical Centre @IIUM is equipped with these tests. This study aimed to determine the prevalence of the different diagnoses of balance disorders in a specialized Vestibular Clinic in Kuantan, Malaysia. MATERIALS AND METHODS: This is a retrospective review of 121 walk-in patients over an 18-month period at a specialized Vestibular Clinic in Sultan Ahmad Shah Medical Centre @IIUM. The variables analysed in this review included the age, gender, ethnicity, diagnoses, and total number of visits before diagnoses were achieved. RESULTS: Meticulous history taking, focused otorhinolaryngological examination and detailed vestibular assessment through the specialized Vestibular Clinic helps us in reaching a conclusive diagnosis. The most common cause of balance disorders in our review was Benign Paroxysmal Positional Vertigo (BPPV), constituting 41.3% of the cases. Among the canals, the posterior canal is the most affected (70%) and is usually treated with Epley manoeuvre. Other common diagnoses include Vestibular Migraine, Meniere’s Disease and Vestibular Neuritis. CONCLUSION: Vestibular clinics play a vital role in helping to pinpoint the accurate diagnosis of patients with balance disorders.